Photobiomodulation increases intrusion tooth movement and modulates IL‐6, IL‐8 and IL‐1β expression during orthodontically bone remodeling. Issue 10 (8th July 2019) - Fernandes, Marcella R. U.; Suzuki, Selly S.; Suzuki, Hideo; Martinez, Elizabeth F.; Garcez, Aguinaldo S.
Abstract: This study investigated the effects of photobiomodulation (PBM) on upper molar intrusion movement, regarding acceleration of orthodontic movement and its molecular effects. The sample consisted of 30 patients with indication of tooth intrusion for oral rehabilitation. Teeth were divided into three different groups: G1 (n = 10) pre‐molars without force or laser application (control); G2 (n = 10) upper molar intrusion; and G3 (n = 10) upper molar intrusion and PBM. On PBM treated molars, the teeth were irradiated with a low‐power diode laser (808 nm, 100 mW), receiving 1 J per point, density of 25 J/cm 2, with application of 10 s per point, 10 points (5 per vestibular and 5 per palatal region). Orthodontic force of intrusion applied every 30 days and PBM was performed immediately, 3 and 7 days after force application for 3 months. Gingival crevicular fluid was collected at the same time periods as the laser applications and interleukins (IL) 1‐β, ‐6 and ‐8 were evaluated by enzyme‐linked immunosorbent assay. Clinical measures were performed monthly to verify the amount of intrusion. The levels of IL‐6, IL‐8 and IL‐1β increased under orthodontic force (G2 and G3) when compared to control group (G1), however, the cytokines levels were significantly higher after PBM (G3). The mean intrusion velocity was 0.26 mm/month in the irradiated group (G3), average duration of 8 months vs 0.17 mm/month for the non‐irradiated group (G2), average duration of 12 months. This study suggests that PBM accelerates tooth movement during molar intrusion, due to modulation of IL‐6, IL‐8 and IL‐1β during bone remodeling. Abstract : The effects of photobiomodulation (PBM) on upper molar intrusion movement, regarding acceleration of orthodontic movement and its molecular effects were investigated. Thirty patients with indication of tooth intrusion were selected and divided into three groups: pre‐molars without force or laser application; upper molar intrusion and upper molar intrusion associated with PBM. It was concluded that PBM accelerates tooth movement during molar intrusion, due to modulation of cytokines during bone remodeling. PBM applied on five different points (buccal and palatal) on upper molars to accelerate tooth movement.